Influence of the Laboratory Equipment Mutual Arrangement and an Infrared Emitter on the Heat Transfer Processes in a Heated Room; AIP Conference Proceedings; Vol. 2337 : Thermophysical Basis of Energy Technologies (TBET 2020) - Borisov B. V. Boris Vladimirovich (Technical thermal physics and nuclear energy, 2021)
Title screen